2000
DOI: 10.1038/35003235
|View full text |Cite
|
Sign up to set email alerts
|

Cbl-b regulates the CD28 dependence of T-cell activation

Abstract: Whereas co-stimulation of the T-cell antigen receptor (TCR) and CD28 triggers T-cell activation, stimulation of the TCR alone may result in an anergic state or T-cell deletion, both possible mechanisms of tolerance induction. Here we show that T cells that are deficient in the adaptor molecule Cbl-b (ref. 3) do not require CD28 engagement for interleukin-2 production, and that the Cbl-b-null mutation (Cbl-b(-/-)) fully restores T-cell-dependent antibody responses in CD28-/- mice. The main TCR signalling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
638
8
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 562 publications
(688 citation statements)
references
References 25 publications
38
638
8
1
Order By: Relevance
“…Consistent with the negative regulation assigned to the Cbl family of proteins, T cells from c-Cbl À/À and Cbl-b À/À mice were hyperactive upon TCR engagement, although some biochemical distinctions between the phenotypes exist [21][22][23][24][25]. T cells from double-knockout mice lacking both c-Cbl and Cbl-b failed to modulate surface TCR after ligand engagement, resulting in sustained TCR signaling and ERK1/2 phosphorylation.…”
Section: Introductionmentioning
confidence: 82%
“…Consistent with the negative regulation assigned to the Cbl family of proteins, T cells from c-Cbl À/À and Cbl-b À/À mice were hyperactive upon TCR engagement, although some biochemical distinctions between the phenotypes exist [21][22][23][24][25]. T cells from double-knockout mice lacking both c-Cbl and Cbl-b failed to modulate surface TCR after ligand engagement, resulting in sustained TCR signaling and ERK1/2 phosphorylation.…”
Section: Introductionmentioning
confidence: 82%
“…Nevertheless, the finding of Rac-1 regu- lates fibronectin-mediated binding of T cells from MS patients may help to bring together several previous findings. Specifically, Vav, a guanine exchange factor that negatively regulates the active (GTP-bound) state of Rac-1 [35], and Cbl-b, which negatively regulates Vav in the development of autoimmunity [36], have been associated with MS. Although our efforts here focused on downstream functional implications of Rac-1/CYFIP2 activation (cell adhesion), studies have indicated that activation of any of several signaling events involved in the T cell receptor or CD28-mediated activation (and thus, Rac-1 activation) plays a prominent role in driving the T cell activation associated with MS.…”
Section: Discussionmentioning
confidence: 99%
“…The RING-type E3 ligase Cbl-b (Casitas B-cell lymphoma-b) was the first identified E3 ligase involved in T-cell activation and tolerance in vivo [32][33][34]. Ablation of Cbl-b renders peripheral T cells hyperproliferative and able to be fully activated in the absence of CD28 co-stimulation, suggesting that Cbl-b is a critical modulator of T cells, uncoupling T-cell activation from the requirement of costimulation [32,33,35].…”
Section: Physiological and Molecular Roles Of E3 Ligases In T-cell Tomentioning
confidence: 99%
“…Ablation of Cbl-b renders peripheral T cells hyperproliferative and able to be fully activated in the absence of CD28 co-stimulation, suggesting that Cbl-b is a critical modulator of T cells, uncoupling T-cell activation from the requirement of costimulation [32,33,35]. At the molecular level, Cbl-b-mediated ubiquitylation of p85, the catalytic subunit of PI3K, alters its intracellular localization, thereby preventing its interaction with CD28 and TCRz at the plasma membrane.…”
Section: Physiological and Molecular Roles Of E3 Ligases In T-cell Tomentioning
confidence: 99%